Mo-Mn bimetallic single atomic cluster catalyst, preparation method and application of Mo-Mn bimetallic single atomic cluster catalyst in lithium-sulfur battery diaphragm

By using Mo-Mn bimetallic single-atom cluster catalyst on the lithium-sulfur battery separator, the problem of lithium polysulfide shuttle effect and slow reaction kinetics during the cycle process is solved, and the capacity, magnification and cycle life of the battery are significantly improved.

CN119725982AActive Publication Date: 2025-03-28SOUTHWEST JIAOTONG UNIV

Patent Information

Application Number
CN202411903824.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

During the circulation process, lithium-sulfur batteries face the problems of lithium polysulfide shuttle effect and slow kinetics of sulfur redox reactions, resulting in low utilization rate of active sulfur and severe capacity decay, which damages battery life.

Method used

The Celgard separator of lithium sulfur batteries was modified by using Mo-Mn bimetallic single-atom cluster catalyst. The catalyst was prepared by high-temperature cracking and ultrasonic dispersion, and attached to the separator to improve catalytic activity and reaction efficiency.

Benefits of technology

The capacity, magnification and cycle life of lithium sulfur batteries have been significantly improved. The discharge capacity of the first round is as high as 1434mAhg-1, and there is still 1014mAhg-1 after 100 cycles, and it also shows good battery performance under extreme cycle conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725982A_ABST
    Figure CN119725982A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium-sulfur batteries, and discloses a Mo-Mn bimetallic single atomic cluster catalyst, a preparation method and application of the Mo-Mn bimetallic single atomic cluster catalyst in a lithium-sulfur battery diaphragm. The preparation method comprises the following steps: self-assembling and positioning metal ions and organic ligands to form a precursor, sintering an organic material through the cracking operation under a heating condition to obtain a nitrogen-rich carbon carrier, naturally cooling, and successfully synthesizing the Mo-Mn bimetallic single atomic cluster catalyst through characterization methods such as an X-ray diffraction pattern and a transmission electron microscope. And carrying out suction filtration on the obtained target sample to a Celgard diaphragm to prepare the lithium-sulfur battery functional diaphragm. The problem of low utilization rate of active sulfur in lithium-sulfur battery circulation can be effectively improved, and conversion and decomposition of polysulfide are promoted, so that the cycle performance of the lithium-sulfur battery is improved, and guidance is provided for further design and development of novel efficient electro-catalysis of the lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-sulfur batteries, and in particular to a Mo-Mn bimetallic single atom cluster catalyst, a preparation method and application thereof in a lithium-sulfur battery separator. Background Art

[0002] Since lithium-sulfur batteries have a very high theoretical specific capacity (1675 mAhg -1 ), excellent long-cycle stability, sustainability and cost-effectiveness, as well as environmentally friendly and abundant sulfur resources, are considered to be one of the important development directions for the next generation of high-energy-density rechargeable batteries. However, practical lithium-sulfur batteries still face major challenges: the electrical insulation of elemental sulfur and its discharge product lithium sulfide, dendrite growth of lithium metal anode, volume strain during cycling, slow reaction kinetics during sulfur redox, and soluble lithium polysulfide shuttling will all lead to low utilization of active sulfur and severe capacity decay, ultimately damaging battery life. The problems of lithium polysulfide shuttling effect and sluggish sulfur redox reaction kinetics during the cycling of lithium-sulfur batteries can be solved by introducing highly active electrocatalysts to accelerate the rapid conversion of polysulfide species.

[0003] Single-atom catalysts have the characteristics of high atomic utilization, clear local coordination structure and high intrinsic catalytic activity. They can efficiently catalyze the conversion of lithium polysulfide while adsorbing soluble lithium polysulfide, thereby inhibiting the shuttle effect and reducing capacity decay to improve the cycle life of lithium-sulfur batteries.

[0004] However, the overall catalytic activity of single-atom catalysts is usually limited by the low metal site concentration (generally no more than 10%). To solve the above problem, cluster catalysts are introduced on the basis of single-atom catalysts. Such catalysts can increase the concentration of active sites and thus improve the overall intrinsic electrocatalytic activity. Therefore, the combination of single-atom catalysts and cluster catalysts is expected to significantly improve the catalytic conversion capacity of lithium polysulfide in lithium-sulfur batteries, inhibit the shuttle effect, and improve the utilization rate of active sulfur, thereby accelerating the practical application of lithium-sulfur batteries. Summary of the invention

[0005] In view of the insufficiency of existing research on the above-mentioned issues, the present invention provides a Mo-Mn bimetallic single atom cluster catalyst material to modify the Celgard diaphragm of a lithium-sulfur battery, so as to achieve high capacity, high rate and long cycle life of the lithium-sulfur battery.

[0006] In order to achieve the above objectives, the present invention provides the following technical solutions:

[0007] A method for preparing a Mo-Mn bimetallic single atom cluster catalyst comprises the following steps:

[0008] Step 1: Preparation of precursor

[0009] (1) manganese nitrate and molybdenum acetylacetonate are used as a manganese source and a molybdenum source, respectively, and zinc nitrate hexahydrate are mixed in proportion, and then stirred with methanol as a solvent, and then a 2-methylimidazole / methanol dispersion is added to the above mixture, and the mixture is continuously and rapidly stirred at room temperature until it is uniformly mixed;

[0010] (2) After the solution obtained in (1) is stirred, it is centrifuged and washed with methanol, and dried overnight in a vacuum drying oven to obtain the desired precursor.

[0011] Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst

[0012] (1) The precursor in step 1 is subjected to a high temperature cracking operation in an inert gas atmosphere with a program-controlled heating rate to obtain a black powder of a Mo-Mn bimetallic single atom cluster catalyst;

[0013] (2) The powder obtained in (1) is added with a binder and a dispersion liquid, and then ultrasonically dispersed. After the dispersion is completed, the powder is attached to a Celgard membrane by vacuum filtration to obtain a Mo-Mn bimetallic single atom cluster functional membrane.

[0014] Furthermore, the manganese source and molybdenum source used in step 1 (1) are one or both of a 50% by mass solution of manganese nitrate and molybdenum acetylacetonate, and the used masses are 1-3 g and 0.05-0.15 g, respectively.

[0015] Furthermore, the methanol used in step (2) is centrifuged 3 to 5 times, and the drying temperature is 50 to 60° C., and the drying time is 24 hours.

[0016] Furthermore, the heating atmosphere used in step 2 (1) is argon or nitrogen.

[0017] Furthermore, in step 2 (1), the heating rate is 2-3°C / min, the pyrolysis temperature is 800-950°C, and the holding time is 3-5h.

[0018] Furthermore, the binder used in step 2 (2) is an acrylonitrile multipolymer (with a mass fraction of 5%).

[0019] Furthermore, in step 2 (2), the dispersion liquid is 70-80 mL of isopropanol and 20-30 mL of deionized water, and the ultrasonic time is 30 min to 60 min.

[0020] Furthermore, in step 2 (2), the filtration volume is 30 mL to 60 mL.

[0021] The present invention also provides a use of the Mo-Mn bimetallic single atom cluster catalyst described in claim 9 in a lithium-sulfur battery separator.

[0022] Compared with the prior art, the technical advantages of the present invention are:

[0023] (1) A preparation method of a Mo-Mn bimetallic single atom cluster catalyst provided by the present invention is based on a zeolite imidazolate framework structure material, and uses manganese nitrate and molybdenum acetylacetonate as metal center sources. After sufficient stirring and centrifugation, a MoMn-ZIF-8 precursor is obtained. The subsequent catalyst powder is cracked and calcined by the precursor. The preparation process is simple, the process is simple, the yield is sufficient, and the repeatability is good, which is conducive to efficient mass production.

[0024] (2) The Mo-Mn bimetallic single atom cluster catalyst provided by the present invention is a manganese and molybdenum bimetallic nitrogen-rich carbon material with a large specific surface area and a stable structure, and has significant advantages in both local atomic structure and microscopic morphology.

[0025] (3) The Mo-Mn bimetallic single atom cluster catalyst provided by the present invention can be used to prepare a functional diaphragm for a lithium-sulfur battery to improve the redox reaction kinetics of the sulfur electrode. The improved diaphragm of the present invention is used to assemble a lithium-sulfur battery. At a discharge rate of 0.2C (1C = 1675mAg -1 ) under the condition of the first cycle discharge capacity up to 1434mAhg -1 , after 100 cycles, there is still 1014mAhg -1 To test extreme cycle conditions, at a 3C charge and discharge rate, the reversible discharge capacity is still 510 mAh g after 1000 cycles. -1 (At this time, the battery without catalyst-modified diaphragm was damaged after 700 cycles as a comparison), showing high battery capacity and excellent cycle stability. At the same time, the functional diaphragm made by the present invention can increase the sulfur positive electrode loading of lithium-sulfur battery to 7.07 mg cm -2 , it can still maintain 5.5mAhcm after 70 cycles -2 The discharge surface capacity has the potential for application in commercial lithium-sulfur battery separators. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 X-ray diffraction (XRD) patterns of the precursors prepared in Examples 1, 2 and 3 of the present invention, respectively;

[0027] Figure 2 The X-ray diffraction (XRD) patterns of the catalysts prepared in Examples 1, 2 and 3 of the present invention, respectively;

[0028] Figure 3 The specific surface area adsorption-desorption curves of the catalysts prepared in Examples 1, 2 and 3 of the present invention are shown respectively;

[0029] Figure 4These are the visualized adsorption experimental images of lithium polysulfide catalysts prepared in Examples 1, 2, and 3 of the present invention, respectively;

[0030] Figure 5 This is an experimental image of an H-type electrolytic cell with a catalyst functional membrane prepared in Example 1 of the present invention;

[0031] Figure 6 This is a field emission scanning electron microscope image of a cross section of the catalyst functional diaphragm prepared in Example 1 of the present invention;

[0032] Figure 7 The contact angle experimental images of the catalyst functional membranes prepared in Examples 1, 2 and 3 of the present invention are shown respectively;

[0033] Figure 8 This is a field emission scanning electron microscope image of the catalyst prepared in Example 1 of the present invention;

[0034] Fig. 9 This is a high-resolution transmission electron microscope image of the catalyst prepared in Example 1 of the present invention;

[0035] Fig.10 The long cycle curve and coulomb efficiency diagram of button-type lithium-sulfur batteries assembled with functional diaphragms prepared in Examples 1, 2 and 3 of the present invention at a rate of 0.2C;

[0036] Fig.11 The long cycle curve and coulombic efficiency diagram of a button-type lithium-sulfur battery assembled with a catalyst functional diaphragm and a high sulfur-loading positive electrode prepared in Example 1 of the present invention at a rate of 0.1C;

[0037] Fig.12 The figure is a comparison of the electrochemical performance of Example 1 of the present invention and a series of catalyst functional membranes for lithium-sulfur batteries reported in the literature. DETAILED DESCRIPTION

[0038] The following will be combined with embodiments 1 to 4 of the present invention and the attached Figures 1 to 12 , the technical solution of the present invention is described in detail. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0039] Embodiment 1:

[0040] A method for preparing a Mo-Mn bimetallic single atom cluster catalyst comprises the following steps:

[0041] Step 1: Preparation of precursor

[0042] (1) 0.0663 g of manganese nitrate and 0.0604 g of molybdenum acetylacetonate as a manganese source and a molybdenum source, respectively, and 1.3772 g of zinc nitrate hexahydrate were added to a beaker and stirred with 100 mL of methanol as a solvent. 3.245 g of 2-methylimidazole was completely dissolved in 100 mL of methanol and then added to the mixture. The mixture was stirred rapidly at room temperature until uniformly mixed.

[0043] (2) After the solution obtained in (1) is stirred, it is centrifuged and washed 5 times with methanol, and dried overnight at 60° C. in a vacuum drying oven to obtain the desired precursor. The X-ray diffraction spectrum of the precursor is shown in FIG. Figure 1 As shown (Example 1 is represented as MoMn-NC in the figure).

[0044] Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst

[0045] (1) The precursor in step 1 is heated to 950°C under an inert gas with a program-controlled heating rate of 2°C / min and kept at this temperature for 3 hours. After the cracking is completed, the temperature is naturally cooled to obtain a black powder of Mo-Mn bimetallic single atom cluster catalyst. The X-ray diffraction spectrum and field emission electron microscope image of the product are shown in Figure 2 , Figure 8 As shown (Example 1 is represented as MoMn-NC in the figure).

[0046] Take 50 mg of the sample for specific surface area test, the results are as follows Figure 3 As shown, the specific surface area of ​​the product is 926m 2 g -1 , a larger specific surface area will be conducive to the adsorption of polysulfide. Then take 50 mg of the product at the bottom of the glass bottle, add electrolyte containing Li2S6 to perform visual adsorption experiment, and then take the supernatant after adsorption for X-ray photoelectron spectroscopy test. The results are as follows Figure 4 As shown (Example 1 is represented as MoMn-NC in the figure), the supernatant S6 in the MoMn-NC group - The signal is the smallest, proving that it has the best adsorption effect on polysulfides.

[0047] The powder was dispersed in ethanol and characterized by high-resolution transmission electron microscopy. Fig. 9 As shown, no crystal structure was observed, which was consistent with the X-ray diffraction pattern.

[0048] (2) The powder obtained in (1) was added with 480uL of acrylonitrile multipolymer (mass fraction 5%) binder, 75mL of isopropanol and 25mL of deionized water as dispersion liquid, and then ultrasonicated for 60min. After the dispersion was completed, 40mL was vacuum filtered and attached to a blank Celgard membrane to obtain a membrane with Mo-Mn bimetallic single atom cluster catalyst.

[0049] Conduct H-type electrolytic cell experiment: Figure 5 As shown in the figure (Example 1 is represented as MoMn-NC in the figure), the prepared diaphragm is clamped in the connecting part of the left and right glass containers of the H-type electrolytic cell, an electrolyte containing polysulfide is added to the left side of the container, and an electrolyte without polysulfide is added to the right side to simulate the diffusion of polysulfide. The results show that compared with the blank diaphragm, the prepared catalyst diaphragm has an inhibitory effect on the diffusion of polysulfide.

[0050] The prepared catalyst membrane was cut open after rapid cooling with liquid nitrogen, and the membrane cross section was characterized by field emission scanning electron microscopy, such as Figure 6 As shown, it is proved that the catalyst material can be uniformly attached to the diaphragm and the average cross-sectional width is 16um.

[0051] The contact angle test of the prepared catalyst membrane was carried out. 1uL of electrolyte was dropped on the surface of the membrane and then photographed by a high frame rate camera. The results are as follows: Figure 7 As shown (Example 1 corresponds to MoMn-NC in the figure), the contact angle of the catalyst is 15.068°, indicating that it has good contact properties with the electrolyte.

[0052] The catalyst functional membrane and the normal sulfur-loaded positive electrode sheet were assembled into a battery for performance testing. Fig.10 (Example 1 corresponds to MoMn-NC in the figure).

[0053] The catalyst functional membrane and the high-load sulfur positive electrode sheet were assembled into a battery for performance testing. Fig.11 , the positive electrode loading is 7.07 mg cm -1 The high cycle performance is still maintained under the condition of

[0054] The performance of the lithium-sulfur battery assembled with the catalyst membrane prepared in this example is compared with the performance of the existing membrane research. Fig.12 As shown, the lithium-sulfur battery assembled with Mo-Mn bimetallic single atom cluster catalyst membrane has the advantages of high rate cycling stability, long cycle life and high discharge specific capacity.

[0055] Embodiment 2:

[0056] A method for preparing a Mo-Mn bimetallic single atom cluster catalyst comprises the following steps:

[0057] Step 1: Preparation of precursor

[0058] (1) 0.1208 g of molybdenum acetylacetonate and 1.3772 g of zinc nitrate hexahydrate were added to a beaker and stirred with 100 mL of methanol as a solvent. 3.245 g of 2-methylimidazole was completely dissolved in 100 mL of methanol and then added to the mixture. The mixture was stirred rapidly at room temperature until uniformly mixed.

[0059] (2) After the solution obtained in (1) is stirred, it is centrifuged and washed 5 times with methanol, and dried overnight at 60° C. in a vacuum drying oven to obtain the desired precursor. The X-ray diffraction spectrum of the precursor is shown in FIG. Figure 1 As shown (Example 2 is represented as Mo-NC in the figure).

[0060] Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst

[0061] (1) The precursor in step 1 is heated to 950°C under an inert gas with a program-controlled heating rate of 2°C / min and kept at this temperature for 3 hours. After the cracking is completed, the temperature is naturally cooled to obtain a black powder of Mo-Mn bimetallic single atom cluster catalyst. The X-ray diffraction spectrum and field emission electron microscope image of the product are shown in Figure 2 , Figure 8 As shown (Example 2 is represented as Mo-NC in the figure).

[0062] Take 50 mg of the sample for specific surface area test, the results are as follows Figure 3 As shown, the specific surface area of ​​the product is 661m 2 g -1 Then, 50 mg of the product was taken at the bottom of a glass bottle, and an electrolyte containing Li2S6 was added to perform a visual adsorption experiment. The supernatant after adsorption was then taken for X-ray photoelectron spectroscopy test. The results are as follows: Figure 4 As shown (Example 2 is represented as Mo-NC in the figure).

[0063] (2) The powder obtained in (1) was added with 480uL of acrylonitrile multipolymer (mass fraction 5%) as a binder, 75mL of isopropanol and 25mL of deionized water as a dispersion liquid, and then ultrasonicated for 60min. After the dispersion was completed, 40mL was vacuum filtered and attached to a blank Celgard membrane to obtain a membrane with Mo-Mn bimetallic single atom cluster catalyst function.

[0064] The contact angle test of the prepared catalyst membrane was carried out. 1uL of electrolyte was dropped on the surface of the membrane and then photographed by a high frame rate camera. The results are as follows: Figure 7As shown (Example 2 corresponds to Mo-NC in the figure), the contact angle of the catalyst is 15.578°.

[0065] The catalyst functional membrane and the sulfur positive electrode are assembled into a battery for performance testing. Fig.10 (Example 2 corresponds to Mo-NC in the figure).

[0066] Embodiment 3:

[0067] A method for preparing a Mo-Mn bimetallic single atom cluster catalyst comprises the following steps:

[0068] Step 1: Preparation of precursor

[0069] (1) 0.1326 g of manganese nitrate solution and 1.3772 g of zinc nitrate hexahydrate were added to a beaker and stirred with 100 mL of methanol as a solvent. 3.245 g of 2-methylimidazole was completely dissolved in 100 mL of methanol and then added to the mixture. The mixture was stirred rapidly at room temperature until uniformly mixed.

[0070] (2) After the solution obtained in (1) is stirred, it is centrifuged and washed 5 times with methanol, and dried overnight at 60° C. in a vacuum drying oven to obtain the desired precursor. The X-ray diffraction spectrum of the precursor is shown in FIG. Figure 1 As shown (Example 3 is represented as Mn-NC in the figure).

[0071] Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst

[0072] (1) The precursor in step 1 is heated to 950°C under an inert gas with a program-controlled heating rate of 2°C / min and kept at this temperature for 3 hours. After the cracking is completed, the temperature is naturally cooled to obtain a black powder of Mo-Mn bimetallic single atom cluster catalyst. The X-ray diffraction spectrum and field emission electron microscope image of the product are shown in Figure 2 , Figure 8 As shown (Example 3 is represented as Mn-NC in the figure).

[0073] Take 50 mg of the sample for specific surface area test, the results are as follows Figure 3 As shown, the specific surface area of ​​the product is 1167m 2 g -1 Then, 50 mg of the product was taken at the bottom of a glass bottle, and an electrolyte containing Li2S6 was added to perform a visual adsorption experiment. The supernatant after adsorption was then taken for X-ray photoelectron spectroscopy test. The results are as follows: Figure 4 As shown (Example 3 is represented as Mn-NC in the figure).

[0074] (2) The powder obtained in (1) was added with 480uL of acrylonitrile multipolymer (mass fraction 5%) as a binder, 75mL of isopropanol and 25mL of deionized water as a dispersion liquid, and then ultrasonicated for 60min. After the dispersion was completed, 40mL was vacuum filtered and attached to a blank Celgard membrane to obtain a membrane with Mo-Mn bimetallic single atom cluster catalyst function.

[0075] The contact angle test of the prepared catalyst membrane was carried out. 1uL of electrolyte was dropped on the surface of the membrane and then photographed by a high frame rate camera. The results are as follows: Figure 7 As shown (Example 3 corresponds to Mn-NC in the figure), the contact angle of the catalyst is 16.346°.

[0076] The catalyst functional membrane and the sulfur positive electrode are assembled into a battery for performance testing. Fig.10 (Example 3 corresponds to Mn-NC in the figure).

[0077] Embodiment 4:

[0078] A method for preparing a Mo-Mn bimetallic single atom cluster catalyst comprises the following steps:

[0079] Step 1: Preparation of precursor

[0080] (1) Add 0.0663 g of manganese nitrate, 0.0604 g of molybdenum acetylacetonate and 1.3772 g of zinc nitrate hexahydrate to a beaker, stir with 100 mL of methanol as a solvent, and then add 3.245 g of 2-methylimidazole completely dissolved in 100 mL of methanol to the mixture, and continue to stir rapidly at room temperature until uniformly mixed.

[0081] (2) After the solution obtained in (1) is stirred, it is centrifuged and washed five times with methanol, and dried overnight at 60° C. in a vacuum drying oven to obtain the desired precursor.

[0082] Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst

[0083] (1) The precursor in step 1 is heated to 950°C under an inert gas with a program-controlled heating rate of 2°C / min and kept warm for 3 hours. After the cracking is completed, the temperature is naturally cooled to obtain a black powder of the Mo-Mn bimetallic single atom cluster catalyst.

[0084] (2) The powder obtained in (1) was added with 480uL of acrylonitrile multipolymer (mass fraction 5%) as a binder, 75mL of ethanol and 25mL of deionized water as a dispersion liquid, and then ultrasonicated for 60min. After the dispersion was completed, 50mL was attached to a blank Celgard membrane by vacuum filtration to obtain a membrane with Mo-Mn bimetallic single atom cluster catalyst function.

[0085] Embodiment 5:

[0086] A method for preparing a Mo-Mn bimetallic single atom cluster catalyst comprises the following steps:

[0087] Step 1: Preparation of precursor

[0088] (1) Add 0.0663 g of manganese nitrate, 0.0604 g of molybdenum acetylacetonate and 1.3772 g of zinc nitrate to a beaker, stir with 100 mL of methanol as a solvent, and then completely dissolve 3.245 g of 2-methylimidazole in 100 mL of methanol and add the mixture to the mixture. Continue to stir rapidly at room temperature until the mixture is evenly mixed.

[0089] (2) After the solution obtained in (1) is stirred, it is centrifuged and washed five times with methanol, and dried overnight at 80° C. in a vacuum drying oven to obtain the desired precursor.

[0090] Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst

[0091] (1) The precursor in step 1 is heated to 800°C under an inert gas with a program-controlled heating rate of 2°C / min and kept warm for 3 hours. After the cracking is completed, the temperature is naturally cooled to obtain a black powder of the Mo-Mn bimetallic single atom cluster catalyst.

[0092] (2) The powder obtained in (1) was added with 360uL of acrylonitrile multipolymer (mass fraction 5%) as a binder, 75mL of ethanol and 25mL of deionized water as a dispersion liquid, and then ultrasonicated for 30min. After the dispersion was completed, 50mL of the powder was attached to a blank Celgard membrane by vacuum filtration to obtain a membrane with Mo-Mn bimetallic single atom cluster catalyst function.

[0093] Embodiment 6:

[0094] A method for preparing a Mo-Mn bimetallic single atom cluster catalyst comprises the following steps:

[0095] Step 1: Preparation of precursor

[0096] (1) Compounds of two metal elements, 0.0663 g of manganese nitrate, 0.0604 g of molybdenum acetylacetonate and 1.02 g of zinc nitrate hexahydrate, were added to a beaker and stirred with 50 mL of methanol as a solvent. 1.12 g of 2-methylimidazole was completely dissolved in 50 mL of methanol and then added to the mixture. The mixture was stirred rapidly at room temperature until uniformly mixed.

[0097] (2) After the solution obtained in (1) is stirred, it is centrifuged and washed five times with methanol, and dried overnight at 60° C. in a vacuum drying oven to obtain the desired precursor.

[0098] Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst

[0099] (1) The precursor in step 1 is heated to 950°C under an inert gas with a program-controlled heating rate of 2°C / min and kept warm for 3 hours. After the cracking is completed, the temperature is naturally cooled to obtain a black powder of the Mo-Mn bimetallic single atom cluster catalyst.

[0100] (2) The powder obtained in (1) was added with 480uL of acrylonitrile multipolymer (mass fraction 5%) as a binder, 75mL of ethanol and 25mL of deionized water as a dispersion liquid, and then ultrasonicated for 30min. After the dispersion was completed, 50mL of the powder was attached to a blank Celgard membrane by vacuum filtration to obtain a membrane with Mo-Mn bimetallic single atom cluster catalyst function.

Claims

1. A method for preparing a Mo-Mn bimetallic single atom cluster catalyst, comprising the following steps: Step 1: Preparation of precursor (1) manganese nitrate and molybdenum acetylacetonate are used as a manganese source and a molybdenum source, respectively, and zinc nitrate hexahydrate are mixed in proportion, and then stirred with methanol as a solvent, and then a 2-methylimidazole / methanol dispersion is added to the above mixture, and the mixture is continuously and rapidly stirred at room temperature until it is uniformly mixed; (2) After the solution obtained in (1) is stirred, it is centrifuged and washed with methanol, and dried overnight in a vacuum drying oven to obtain the desired precursor; Step 2: Preparation of Mo-Mn bimetallic single atom cluster catalyst (1) The precursor in step 1 is subjected to a high temperature cracking operation in an inert gas atmosphere with a program-controlled heating rate to obtain a black powder of a Mo-Mn bimetallic single atom cluster catalyst; (2) The powder obtained in (1) is added with a binder and a dispersion liquid, and then ultrasonically dispersed. After the dispersion is completed, the powder is attached to a Celgard membrane by vacuum filtration to obtain a Mo-Mn bimetallic single atom cluster functional membrane.

2. The method for preparing a Mo-Mn bimetallic single atom cluster catalyst according to claim 1, characterized in that: The manganese source and molybdenum source used in step 1 (1) are one or both of a 50% by mass manganese nitrate solution and molybdenum acetylacetonate, and the used masses are 1-3g and 0.05-0.15g respectively.

3. The method for preparing a Mo-Mn bimetallic single atom cluster catalyst according to claim 1, characterized in that: The methanol used in step 1 (2) is centrifuged 3 to 5 times, and the drying temperature is 50 to 60° C. and the drying time is 24 hours.

4. The method for preparing a Mo-Mn bimetallic single atom cluster catalyst according to claim 1, characterized in that: The heating atmosphere used in step 2 (1) is argon or nitrogen.

5. The method for preparing a Mo-Mn bimetallic single atom cluster catalyst according to claim 1, characterized in that: In step 2 (1), the heating rate is 2-3°C / min, the pyrolysis temperature is 800-950°C, and the holding time is 3-5h.

6. The method for preparing a Mo-Mn bimetallic single atom cluster catalyst according to claim 1, characterized in that: The binder used in step 2 (2) is an acrylonitrile multipolymer.

7. The method for preparing a Mo-Mn bimetallic single atom cluster catalyst according to claim 1, characterized in that: In step 2 (2), the dispersion liquid is 70-80 mL of isopropanol and 20-30 mL of deionized water, and the ultrasonic time is 30 min to 60 min.

8. The method for preparing a Mo-Mn bimetallic single atom cluster catalyst according to claim 1, characterized in that: The filtration volume in step 2 (2) is 30 mL to 60 mL.

9. A Mo-Mn bimetallic single atom cluster catalyst prepared by the method according to any one of claims 1 to 8.

10. Use of the Mo-Mn bimetallic single atom cluster catalyst according to claim 9 in a lithium-sulfur battery separator.

Citation Information

Patent Citations

  • Lithium-sulfur battery anode host material based on manganese sulfide-molybdenum disulfide heterojunction as well as preparation method and application of lithium-sulfur battery anode host material

    CN115621435A

  • Modified manganese dioxide catalyst, functional diaphragm and preparation method and application thereof

    CN116315448A

  • Preparation method of high-catalytic-activity composite material and application of high-catalytic-activity composite material in lithium-sulfur battery

    CN117038901A

  • Phosphorus-doped hollow MnMoO4 nanosphere lithium oxygen battery positive electrode catalytic material, preparation method thereof and lithium oxygen battery

    CN118336001A

  • Method of manufacturing a catalyst membrane, catalyst membrane obtained thereby and use thereof

    WO2023094287A1

Cited By

  • ZnxMn1-xS infinite solid solution with surface defects, preparation method and application of ZnxMn1-xS infinite solid solution in Li-S battery

    CN122102216A